Mundo de medo: inquisição e cristãos-novos nos espaços coloniais capitanias de Pernambuco, Itamaracá e Paraíba (1593-1595) - Oliveira, Halyson Rodrygo Silva de (2012)
Founded in 1536, the Court of the Holy Office of the Portuguese Inquisition was established as an ecclesiastical institution, but at the same time subordinate to the real powers. Among the main victims of persecution effected by the Holy Office, were the New Christians - Jews forcibly converted in 1497 or their descendants - that due to their socio-religious were repeatedly accused of heresy. This paper conducted a survey that sought to understand the historical performance of the Inquisition in Brazil in the sixteenth century on the New Christians, especially those accused of secretly retaining the religious customs of the Mosaic law, given the investigative and punitive procedures employed by the Inquisition as part of a set of actions that produce social insecurities and producers / broadcasters of fear in the populations under scrutiny. In this sense, the approach was based on the analysis of documents produced on the first visit of inspection performed in Brazil inquisitorial sixteenth century, concerning the captaincy of Pernambuco and Paraiba Itamaracá (1593-1595), not excluding, however, the sources of the first stage of visitation that occurred between 1591-1593 in the province of Bahia de Todos os Santos, even though its use is ancillary and punctual. The objective of this research was to understand the consequences of inquisitorial procedures generated on the imaginary, and the Inquisition, using the expressions and signs of fears relating to individuals contained in the New Christian complaints to the Holy Office as documentary evidence of the fear caused by the Holy Tribunal. The adoption of specific behaviors by the New Christians in the home - these spaces are appropriate and adapted to the detriment of the religious practices of Judaism features - characterizes the spatial perspective of the study, thus indicating a further objective of the study: to understand how the New Christians experienced domestic spaces in a historical context marked by behavioral surveillance generally considered morally condemned and suspected of heresy. The research was conducted to analyze the complaints and quantitative survey of some indices of documentation for the understanding of overall charges and how individuals New Christians were concerned with the domestic space, using them to maintain criptojudaica religiosity, transformed places housing often esnogas, makeshift synagogue for meetings and celebrations of Judaizing New Christians. The formulations of Michel de Certeau on appropriations and meanings of space - presented by the author in the metaphor of "practice areas" - were integrated into the workforce in order to understand the ways in which the New Christians appropriated the colonial houses, designed these spaces a very specific language in the Crypto, in which women are prominent figures. The works of Jean Delumeau and Bartholomé Benassar integrate the discussion of the Inquisition and the sensibilities of fear in the work performed. The analysis allowed the documentation to understand the meaning and the extent related to the general fear that the Inquisition represented. Some complaints are indicative of fears that can be perceived implicitly based on behaviors and attitudes adopted by the New Christians, others, however, are direct expressions of fear caused by allusion or initiative of the actions of the Inquisition in colonial Brazil in the sixteenth century